Morphological Description of a Plankton-Based Megalopa Thalamita sp. (Crustacea: Brachyura: Portunidae) from the Obhur Creek, Red Sea, Saudi Arabia - Effendy, Indra; Kumar, Austin; El-Sherbiny, Mohsen (Journal of King Abdulaziz University: Marine Sciences, 2021)
Megalopae of a Thalamita sp. crab, collected from the Obhur Creek, Jeddah, Saudi Arabia, are morphologically described. The present specimens are compared with megalopae of two species of this genus: Thalamita pelsarti from Japan water and Thalamita crenata from Indian waters. Some morphological features are common for megalopae of Thalamita: 3-segmented antennal peduncle, 8-segmented antennal endopod, 2-segmented endopod of mandible, 5-segmented endopod of maxilliped III and 3 hooks in the endopod of pleopods I–IV. The morphological differences found between the megalopae of Thalamita spp. are found in various appendages of antennule, antenna, maxillule, maxilla, maxillipeds I–III and pleopods.